Novel Copy Number Deletion Involving NUS1 Associated With Epilepsy, Tremor, and Intellectual Disability - Jing Y. Hsu; Daniah H. Ibrahim; Riza Ali; Elaine Marchi; Maureen Gavin; Karen Amble; Gholson J. Lyon (Clinical Case Reports)
ABSTRACT Copy number variations (CNVs) contribute to various disorders including intellectual disability, developmental disorders, and cancer. This study identifies a de novo 2.62 Mb deletion at 6q22.1_q22.31, implicating the NUS1 gene in epilepsy, spinal abnormalities, and intellectual disability, thereby expanding its known phenotypic associations.